Analysis of antioxidant and antigenotoxic activities of artichoke (C. cardunculus L.) natural leaves extracts - Gonçalves, Ana Isabel Pereira (2018)
Dissertação de mestrado em Molecular Biology, Biotechnology and Bioentrepreneurship in Plants